Production of ”Tokolan” White Shrimp Litopenaeus vannamei in the Cage with Different Rearing Density - E. Supriyono; E. Purwanto; N.B.P. Utomo (Jurnal Akuakultur Indonesia, 2007)
Larva rearing is one of the efforts to increase white shrimp Litopenaeus vannamei seed quality.  This study was conducted to determine effect of  rearing density on the quality and productivity of white shrimp larvae in cage system. The tested rearing densities were 500, 1000, 1500 and 2000 ind/m2 and cultured for 28 days.  The result showed that rearing density did not affect survival rate and coefficient of variation of shrimp length. The treatmentonly affected the shrimp larvae growthwhere 500 ind/m2 rearing density gave the best growth.